Corporate Culture in Developing Professionalism of Human Resources in LEMHANNAS RI - Paula Theresia Ekowati Purwaning Utami; Irwan Abdullah; Edhi Martono (Jurnal Studi Pemerintahan, 2012)
Based on a case study by Lemhannas RI, this work attempts to discuss the relation of professionalism of human resources and corporate culture. The change and growth of corporate culture in an organization requires strong commitment from those involved in it. Corporate culture should be continually developed through a persistent socialization, partnership and supervision programs. The right management of human resources, which follows the basis of management, will give a great contribution when applied well. In addition, policy evaluation on corporate culture should include structural and cultural aspects and be conducted in several steps, including identification of goals and ways of completing them, measurement of relevant information activities, analysis of data for a conclusion and recommendation. The recommendation is a crucial step that needs a special attention for the restructurization of culture for better results. This study concludes that interaction between structure and culture is a key and pre-condition for the growth of a better and conducive corporate culture for accomplishing the goals of organization.